BNCC of children education: critical and transgression training needs to trainers (as) in pedagogy courses (Revista Internacional de Formação de Professores, 2019)
The BNCC has been a recurring theme and a driving force for discussions in the educational field, especially in Child Education, always in the perspective of criticism, resistance and suggestion of its revocation, in the name of the implementation of the Diretrizes Curriculares Nacionais. The research problem, of a bibliographic nature, lies in the question: does the BNCC in early childhood education evince, what training needs for trainees in Pedagogy courses? The results point out that critical and transgressive formative actions are urgently required, fundamentally requiring a change of language for the projects of observation and regency and challenges to the guiding teachers and supervisors.
Keywords: BNCC. Children education. Trainers. Pedagogy.